PERCEPTIONS AND ATTITUDES OF INDONESIAN TEACHERS TOWARD COMMUNICATIVE LANGUAGE TEACHING - Selvira Yanti, Gina (Jurnal Ilmiah Spectral, 2019)
This review paper described some documented researches on teachers’ perception and attitudes toward Communicative Language Teaching into some patterns: teachers’ understanding toward CLT concept theoretically, teachers’ implementation of CLT in classrooms, and teachers’ challenges and difficulties in implementing CLT. Instead of taking the existing researches globally, this paper took the ones within the scope of Indonesia in the publication year 2013-2019; therefore, there were eight researches in total. The results showed that most of teachers were favorable to the CLT concepts and most of them showed that they understand CLT, theoretically. In contrast, in practical, many of teachers had been found to be not consistent with what they had claimed about CLT concept; it can be related to some challenges and / difficulties they had been shared such as lack of teaching training, having over workload; students’ tendency not to use the target language; big class size, and grammar based examination. These research reports focused on their own context of their teaching places, thus, the cultures of each setting may affect their perceptions and attitudes toward CLT. This review paper results hopefully can be a good reference for teachers, lecturers in their next researches related to the topic. Moreover, for the decision-makers to be able to take into consideration from some challenges that teachers had been shared into the better next decision or solution to solve it.